Digital Image Misused Protection and Tracking Techniques and Tools - Rahman, Nor Azlina Abd; Amirizal, Mohamad; Hanis, Nursyafiqah (Journal of Applied Technology and Innovation, 2018)
This research focuses on several issues that commonly faced by the Social Media users. Apart from that, discussion on security and awareness that can be considered by the Social Media users to protect their data when uploaded to the Social Media is also included. Data protection mainly covered on digital images and techniques or tools that can be used to protect digital images from being misused by unauthorised party. Detail discussion on how Digital watermarking can be used to the digital images in providing security to users were discussed. Several tools are highlighted such as Copyscape and TinEye that can be used to track of any images misused by unauthorised party.